Efektivitas Penggunaan Macromedia Flash pada Perkuliahan Jarak Jauh Sistematika Tumbuhan Rendah Pendidikan Biologi FKIP Universitas Riau Tahun 2021: (The Effectiveness of Using Macromedia Flash in Long Distance Lectures on Low Plant Systematics Biology Education FKIP Riau University in 2021) - Irda Sayuti; Imam Mahadi; Darmawati Darmawati; Nursal Nursal; Harlis Harlis (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2022)
The purpose of this study was to determine the effectiveness of using macromedia flash in the distance lectures for students of the Biology Education Study Program, FKIP University of Riau in 2021. This media application was applied to learning low-level plant systematics (STR) courses. The research was conducted at the Biology Education Study Program, FKIP Riau University, in the even semester of 2021. The object of the research was 35 students of Class A lectures on low-level plant systematics. The research was conducted using the classroom action method, namely applying macromedia flash learning media. The lecture period is divided into 2 rounds where the first round is learning without using macromedia flash media and the second round using macromedia flash. The indicators set in the form of student learning outcomes during lectures and student responses to the use of macromedia flash. The conclusion of the study is that the use of macromedia flash can improve student learning outcomes with an effectiveness ratio of 83% and is considered effective in terms of learning outcomes. Student responses to the application of macromedia flash media are classified as good with a percentage of 79.91%. Key words: Macromedia flash, Low Plant Systematics, Effectiveness Â Abstrak. Tujuan dari penelitian ini adalah untuk mengetahui efektivitas Penggunaan macromedia flash pada perkuliahan jarak jauh mahasiswa Program Studi Pendidikan biologi FKIP Univeristas Riau tahun 2021. Aplikasi media ini diterapkan pada pembelajaran mata kuliah sistematika tumbuhan tingkat rendah (STR). Penelitian dilakukan di program studi pendidikan biologi FKIP Universitas Riau pada semester genap tahun 2021. Objek penelitian adalah mahasiswa Kelas A oerkuliahan sistematika tumbuhan tingkat rendah sebanyak 35 orang. Penelitian dilakukan dengan metode tindakan kelas yaitu menerapkan media pembelajaran macromedia flash. Masa perkuliahan dibagi dalam 2 putaran dimana putaran pertama adalah pembelajaran tanpa penggunaan media macromedia flash dan putaran kedua dengan menggunakan macromedia flash. Indikator yang ditetapkan berupa hasil belajar mahasiswa selama perkuliahan serta respon mahasiswa terhadap penggunaan macromedia flash.. Kesimpulan dari Penelitian diketahuiÂ bahwa penggunaan macromedia flash dapat meningkatkan hasil belajar mahasiswa dengan rasio efektivitas 83% dan tergolong efektif dari segi hasil pembelajaran. Respon mahasiswa terhadap penerapan media macromedia flash tergolong baik dengan presentase 79.91%. Kata kunci: Macromedia flash, Sistematika Tumbuhan Rendah, Efektivitas